Privacy, labour and law - Ugarte Cataldo, José Luis (2020)
This work analyses -from a strictly legal dimension- two current problems that the confrontation between work and privacy presents: on the one hand, the determination of the protected area of the right to privacy, that is, the content of that right within a labour relationship; thus, a dogmatic wide conception will be sustained, understanding it not only as a secret but also as a right of self-determination. On the other hand, what are the limits of privacy, in order to solve the possible conflicts between this right and those that are recognized to the employer.